Indonesian Folk Music In Piano Compositions: Rapsodia By Jaya Suprana And Ananda Sukarlan - Hendrik L. Simanjuntak; Baharui Halawa; Aryadi Simamora (LPPM Universitas PGRI Sumatera Barat, 2024)
Conditions in Indonesia are actually inversely proportional to the existence of composers in Europe, such as; Bach, Handel, Haydn, Mozart, Beethoven, Listz, Schumann, Schubert, Debussy, Verdi, Ravel, Rachmaninoff, etc. The research explores Indonesian folk music which has become a source of inspiration for Jaya Suprana and Ananda Sukarlan in composing the piano composition Rapsodia. This research also prioritizes musicological studies to see their mindset in 'capturing' or manifesting Indonesian folk music which gives a 'magical touch' in their work. Research uses a qualitative approach with musicological studies. Qualitative research understands what the research subjects experience holistically and by means of descriptions in the form of words and language in a natural context. Based on the results of the musical analysis, it was found that the musical educational background they had taken for decades as well as the various musical activities they had carried out had made a big contribution in terms of considering the musical style they discussed in the musical works they composed. Ananda Sukarlan and Jaya Suprana's musical language still uses traditional musical notation, which means that all their musical ideas and ideas can still be manifested in traditional musical notation without having to provide certain symbols in the work